CRITICAL REVIEW ON THE IMPACT OF PHARMACOGENOMICS ON PERSONALIZED MEDICINE AND DRUG THERAPY - Saeed Mohamad Rashed Al Rashadi, Bassam AowdhAlwadaiBalwadai, Abdullah Obeid Salem Al Marwani, Abdulrahman Awadh Alwadai, Khalid Askar Hadi Al Abbas, Abdullah NajiMesferAlalhareth, Saeed Abdulrahman Ali Hafez, Hamad Mohammed Salem Al Ghubari (Chelonian Research Foundation, 2023)
Pharmacogenomics has revolutionized personalized pharmaceutical and medical treatment, considering how a person's hereditary cosmetics influence their reaction to drugs. This basic audit looks at its suggestions through writing surveys and examinations. Pharmacogenomics has revolutionized medicine utilization, endorsing persistent results by expanding the adequacy of medicines, lessening antagonistic occasions, and progressing clinical results. Despite this advance, challenges such as taking a toll, availability, and execution stay. Joining pharmacogenomics into clinical hone is essential to optimizing quiet care and guaranteeing appropriate medicine administration. This survey highlights the progressive potential of pharmacogenomics, which tends to require collaborative exertion to overcome current challenges in treatment and make it all around applicable. Keywords: Pharmacogenomics, personalized medicine, drug therapy, genetic cosmetics, drug response, adverse drug reactions, precision medicine.